Non-local slicing approaches for NNLO QCD in MCFM - John M. Campbell; R. Keith Ellis; Satyajit Seth (Journal of High Energy Physics, 2022)
Abstract We present the implementation of several processes at Next-to-Next-to Leading Order (NNLO) accuracy in QCD in the parton-level Monte Carlo program MCFM. The processes treated are pp → H, W ± , Z, W ± H, ZH, W ± γ, Zγ and γγ and, for the first time in the code, W + W − , W ± Z and ZZ. Decays of the unstable bosons are fully included, resulting in a flexible fully differential Monte Carlo code. The NNLO corrections have been calculated using two non-local slicing approaches, isolating the doubly unresolved region by cutting on the zero-jettiness, T $$ \mathcal{T} $$ 0, or on q T , the transverse momentum of the colour singlet final-state particles. We find that for most, but not all processes the q T slicing method leads to smaller power corrections for equal computational burden.